A novel evaluation of endothelial dysfunction ex vivo: "Teaching an Old Drug a New Trick". Issue 21 (10th November 2021) - Jin, Lexiao; Conklin, Daniel J.
Abstract: Cardiovascular disease (CVD) is the leading cause of morbidity and mortality worldwide. Many CVDs begin with endothelium dysfunction (ED), including hypertension, thrombosis, and atherosclerosis. Our assay evaluated ED in isolated murine aorta by quantifying phenylephrine‐induced contractions (PE) in the presence of L‐NAME, which blocked acetylcholine‐induced relaxation (ACh %; >99%). The "L‐NAME PE Contraction Ratio" (PECR) was defined as: "PE Tension post‐L‐NAME" divided by "PE Tension pre‐L‐NAME." We hypothesized that our novel PE Contraction Ratio would strongly correlate with alterations in endothelium function. Validation 1: PECR and ACh % values of naïve aortas were strongly and positively correlated (PECR vs. ACh %, r 2  = 0.91, n  = 7). Validation 2: Retrospective analyses of published aortic PECR and ACh % data of female mice exposed to filtered air, propylene glycol:vegetable glycerin (PG:VG), formaldehyde (FA), or acetaldehyde (AA) for 4d showed that the PECR in air‐exposed mice (PECR = 1.43 ± 0.05, n  = 16) correlated positively with the ACh % ( r 2  = 0.40) as seen in naïve aortas. Similarly, PECR values were significantly decreased in aortas with ED yet retained positive regression coefficients with ACh % (PG:VG r 2  = 0.54; FA r 2  = 0.55). Unlike other toxicants, inhaled AA significantly increased both PECR and ACh % values yet diminished their correlation ( r 2  = 0.09). Validation 3: To assess species‐specific dependence, we tested PECR in rat aorta, and found PECR correlated with ACh % relaxation albeit less well in this aged and dyslipidemic model. Because the PECR reflects NOS function directly, it is a robust measure of both ED and vascular dysfunction. Therefore, it is a complementary index of existing tests of ED that also provides insight into mechanisms of vascular toxicity. Abstract : Endothelial dysfunction (ED) is sine qua non of atherosclerosis and other cardiovascular diseases in humans, yet the mechanisms that contribute to ED are still being investigated. Our study demonstrates a novel methodological twist using an old drug (L‐NAME) to screen for ED in aorta ex vivo.